Pengembangan Hypermedia Bermuatan Ekoliterasi untuk Meningkatkan Prestasi Belajar IPAS Peserta Didik Kelas V SD - Ni Komang Suri Rahayu; Dewa Bagus Sanjaya; I Made Candiasa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
In order to improve the science learning achievement of fifth grade elementary school students, this study aims to create valid, useful, and effective hypermedia containing ecoliteracy. The ADDIE development model is used to develop hypermedia through the stages of analysis, planning, development, implementation, and evaluation. It is crucial to teach ecoliteracy early on, and learning media is one of the factors contributing to the low achievement of elementary school students in science learning. The Learning Object Review Instrument (LORI) instrument is used to test the validity of the material and media. The User Experience Questionnaire (UEQ) instrument is used to test the practicality of hypermedia. The effectiveness of hypermedia is analyzed by a one-tailed t-test. This study produces learning media in the form of hypermedia that can be accessed on a link containing interactive material, games, and evaluation questions. The validity test of the hypermedia material and media obtained very valid results with a score of 4.6 for the material and 4.5 for the media. Practicality test from teachers and students got an average score of 2.5 with superior category, so that hypermedia can be stated as practical in terms of attractiveness, clarity, efficiency, stimulation, accuracy and novelty. Effectiveness test analyzed by one-tailed t-test got tcount result 51.757 which is bigger than ttable 2.068, so hypothesis H1 is accepted. This shows that implementation of hypermedia effectively improves students’ learning achievement in harmonious ecosystem material, so it is suitable to be used in learning process.